ANALISIS KUALITAS PELAYANAN PROGRAM JAMINAN HARI TUA BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN CABANG UNGARAN - Afif Fauziyani Sholiha; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
This research is arranged to know of quality service for old day guarantee programs social security agency (BPJS) Ketenagakerjaan Ungaran Branch. This research uses the type of quantitative descriptive research. The number of samples is 100 participants old day guarantee programs social security agency (BPJS) Ketenagakerjaan Ungaran Branch. This research uses measurement through 5 dimension of servant that is tangible, reliability, responsiveness, assurance, and empathy by comparing between performance (X) and expectation (Y) that cause satisfaction or dissatisfaction. The results of this study indicate that there are three dimensions that are considered good and two dimensions are considered less good in service. Dimensions are: 1. Tangible, with an average value of performance level of 3,68; 2. Responsiveness, with an average performance level of 3,52; 3. Empathy, the average value of performance level of 3,50. While dimensions are considered less that is 1. Reliability, the average value of performance level of 3,23; 2. Assurance, with an average grade of performance of 3,34. Suggestions in this study should include training activities for officers, career development officers through education, staff development by adding tasks and involving officers for comparative studies.